Impact of MPL on Temperature Distribution in Single Polymer Electrolyte Fuel Cell with Various Thicknesses of Polymer Electrolyte Membrane - Akira Nishimura; Tatsuya Okado; Yuya Kojima; Masafumi Hirota; Eric Hu (Energies, 2020)
The impact of micro porous layer (MPL) with various thicknesses of polymer electrolyte membrane (PEM) on heat and mass transfer characteristics, as well as power generation performance of Polymer Electrolyte Fuel Cell (PEFC), is investigated. The in-plane temperature distribution on cathode separator back is also measured by thermocamera. It has been found that the power generation performance is improved by the addition of MPL, especially at higher current density condition irrespective of initial temperature of cell (Tini) and relative humidity condition. However, the improvement is not obvious when the thin PEM (Nafion NRE-211; thickness of 25 μm) is used. The increase in temperature from inlet to outlet without MPL is large compared to that with MPL when using thick PEM, while the difference between without MPL and with MPL is small when using thin PEM. It has been confirmed that the addition of MPL is effective for the improvement of power generation performance of single PEFC operated at higher temperatures than normal. However, the in-plane temperature distribution with MPL is not even.